2020
DOI: 10.1152/ajprenal.00595.2019
|View full text |Cite
|
Sign up to set email alerts
|

Dual blockade of protease-activated receptor 1 and 2 additively ameliorates diabetic kidney disease

Abstract: Protease-activated receptors (PARs) are coagulation protease targets, and they increase expression of inflammatory cytokines and chemokines in various diseases. Of all PARs, previous reports have shown that PAR1 or PAR2 inhibition is protective against diabetic glomerular injury. However, how PAR1 and PAR2 cooperatively contribute to diabetic kidney disease (DKD) pathogenesis and whether dual blockade of PARs is more effective in DKD remain elusive. To address this issue, male type I diabetic Akita mice hetero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 31 publications
0
24
0
Order By: Relevance
“…Moreover, our recent study demonstrated that a natural product sarsasapogenin alleviated DN in rats by downregulating PAR-1 (Tang et al, 2020). Additionally, dual blockade of PAR-1 and PAR-2 additively ameliorates DN in male type 1 diabetic Akita mice (Mitsui et al, 2020). Taken together, PAR-1 plays an important role in the development of DN.…”
Section: Discussionmentioning
confidence: 81%
“…Moreover, our recent study demonstrated that a natural product sarsasapogenin alleviated DN in rats by downregulating PAR-1 (Tang et al, 2020). Additionally, dual blockade of PAR-1 and PAR-2 additively ameliorates DN in male type 1 diabetic Akita mice (Mitsui et al, 2020). Taken together, PAR-1 plays an important role in the development of DN.…”
Section: Discussionmentioning
confidence: 81%
“…Immunohistochemistry for F4/80 were performed as previously described [ 44 ]. We used rat-anti-mouse F4/80 monoclonal antibody (1:200, Clone A3-1, Bio-Rad, Hercules, CA, USA) as the primary antibody.…”
Section: Methodsmentioning
confidence: 99%
“…We have demonstrated that PAR1 and PAR2 cooperatively contribute to DKD pathogenesis (Mitsui et al 2020). In this study, male type I diabetic Akita mice heterozygous for eNOS (Ins2 Akita/+ ; eNOS +/-) were used as a model of DKD.…”
Section: Dual Blockade Of Par1 and Par2 In Diabetic Mice With Reduced Enosmentioning
confidence: 99%
“…We focused on the pro-inflammatory effects of PAR1 and PAR2 agonists on human endothelial cells (Mitsui et al 2020). The results showed that stimulation with both PAR1 and PAR2 agonists synergistically increased the expression levels of MCP1 and PAI1 mRNA.…”
Section: Dual Blockade Of Par1 and Par2 In Diabetic Mice With Reduced Enosmentioning
confidence: 99%